Collection and Analysis of Quantitative Data in the Field of Migration. Past Trends, Current Status and Future Prospects - Wanner, Philippe (Neuchâtel : nccr - on the move, 2020)
To be understood, any social phenomenon must be documented, for example, using statistical indicators or figures. In this article, we show, on the one hand, that the complexity of migratory flows requires new ways of collecting information, fortunately made possible by advances in information technology and the development of data collection methods. On the other hand, using an example of Swiss databases, we indicate the new analytical potential offered by the development of comprehensive data systems. Finally, we discuss the potential offered by private data, in particular social networks and provider data, while also pointing out certain limitations.
Keywords: Population Registers; Demography; Data Sources; Big Data; Longitudinal Approaches